The diversity, extracellular enzymatic activities and photoprotective compounds of yeasts isolated in Antarctica - Vaz, Aline B. M. (2011)
The diversity of yeasts collected from different sites in Antarctica (Admiralty Bay, King George Island and Port Foster Bay and Deception Island) and their ability to produce extracellular enzymes and mycosporines were studied. Samples were collected during the austral summer season, between November 2006 and January 2007, from the rhizosphere of Deschampsia antarctica, ornithogenic (penguin guano) soil, soil, marine and lake sediments, marine water and freshwater from lakes. A total of 89 isolates belonging to the following genera were recovered: Bensingtonia, Candida, Cryptococcus, Debaryomyces, Dioszegia, Exophiala, Filobasidium, Issatchenkia (Pichia), Kodamaea, Leucosporidium, Leucosporidiella, Metschnikowia, Nadsonia, Pichia, Rhodotorula, and Sporidiobolus, and the yeast-like fungi Aureobasidium, Leuconeurospora and Microglossum. Cryptococcus victoriae was the most frequently identified species. Several species isolated in our study have been previously reported to be Antarctic psychophilic yeasts, including Cr. antarcticus, Cr. victoriae, Dioszegia hungarica and Leucosporidium scottii. The cosmopolitan yeast species A. pullulans, C. zeylanoides, D. hansenii, I. orientalis, K. ohmeri, P. guilliermondii, Rh. mucilaginosa, and S. salmonicolor were also isolated. Five possible new species were identified. Sixty percent of the yeasts had at least one detectable extracellular enzymatic activity. Cryptococcus antarcticus, D. aurantiaca, D. crocea, D. hungarica, Dioszegia sp., E. xenobiotica, Rh. glaciales, Rh. laryngis, Microglossum sp. 1 and Microglossum sp. 2 produced mycosporines. Of the yeast isolates, 41.7% produced pigments and/or mycosporines and could be considered adapted to survive in Antarctica. Most of the yeasts had extracellular enzymatic activities at 4 oC and 20 oC, indicating that they could be metabolically active in the sampled substrates.